Half of the mothers had poor delivery referral practices in public hospitals of Bahir Dar City Northwest, Ethiopia - Amare Fenta Abebe; Desta Debalkie Atnafu; Habtamu Alganeh Guadie (Frontiers in Public Health)
BackgroundPolicy makers and stakeholders may benefit from understanding maternal delivery referral practices as they develop efficient mechanisms to implement appropriate referral linkage. However, the practice of maternal delivery referral is not well known. This study aims to assess the maternal referral practices and associated factors among laboring mothers referred to public hospitals of Bahir Dar City, Northwest, Ethiopia.MethodIn the hospitals of the city of Bahir Dar, a facility-based cross-sectional survey was carried out from March 1 to March 30, 2021. A total of 358 mothers who came by referral to give birth at the public hospitals in Bahir Dar were interviewed using a pre-tested questionnaire that was presented by an interviewer. Data was coded, and inputted to Epi-data version 3.1 software, and after being transferred, analyzed using SPSS version 25. The associated factors linked to poor maternal referral practices were identified using bi-variable and multivariable logistic regressions. The p-value cutoff of 0.05 was ultimately determined to be statistically significant.ResultsA total of 353 study participants took part in the study. The level of poor maternal referral practice was 52.7% (95% CI 47%, 58%). The mean age of the respondents was 26.73 (± 5.45) years. Twenty eight percent of the mothers were illiterate. Unable to read and write (AOR = 2.38, 95%CI: 1.15, 4.94), read and write only (AOR = 6.59, 95%CI: 2.53, 17.17), monthly income < 1,527 birr (AOR = 4.55, 95%CI: 1.91, 10.84), monthly income between 1,527 and 3,000 birr (AOR = 4.29, 95%CI: 1.76, 10.50), and monthly income between 3,001 and 5,305 birr (AOR = 3.73, 95%CI: 1.49, 9.33), referred from referral hospitals (AOR = 4.63, 95%CI: 1.94, 11.07), gave birth via cesarean section (AOR = 2.06, 95%CI: 1.22, 3.47), gave birth via assisted delivery (AOR = 4.77, 95%CI: 1.64, 13.91), and time spent more than 1 h to arrive to Bahir Dar City public hospitals (AOR = 2.15, 95%CI: 1.07, 4.34) were significantly associated with poor maternal referral practice.ConclusionPoor maternal referral practices were widespread. The use of maternal referrals was influenced by obstetric, social, environmental, and demographic factors. The poor maternal referral practices during labor should receive the most attention from mothers who have low monthly incomes and do not attend formal education.